Refractive Errors and Visual Anomalies in Schoolchildren in the Kavrepalanchowk District - Marasini, S; Sharma, R; Sthapit, P R; Sharma, D; Koju, U; Thapa, G; Nepal, B P (Kathmandu University Medical Journal, 2012)
Background Schoolchildren form an important target group for a nation, as any ocular morbidity in this age group has huge physical, psychological and socio-economical implications. Childhood eye disorders can contribute to the burden of blindness in any society. This study aims to highlight the prevalence of ocular morbidity in governmental schools in a sub-urbanised area of Nepal, in relation to ethnic variation. Methods A descriptive study, and the study population used were schoolchildren who were examined in their schools and afterwards referred to the hospital if required. Presenting and best corrected visual acuity, refraction, binocularity assessment, anterior and posterior segment evaluation was carried out. Data was analysed statistically using SPSS software, version 14. Results We examined 1,802 school children. The mean age was 10.78±3.61 years. Ocular abnormality was detected in 11.7%. Low vision and blindness was rare (0.11% and 0.05%). Ocular morbidities were more common in Newar communities (3.71%) followed by Brahamans (3.38%). Lid abnormalities were the most common (3.55%), and morbidities in each ethnicity were followed by refractive errors (3%), conjunctival abnormalities (1.10%), strabismus (0.88%) and amblyopia (0.33%). Refractive errors were most common among Newar communities (1.16%) at almost twice as many Brahamans (0.61%) followed by Mongolians (0.49%). Convergence insufficiency was detected in 2.49% (p<0.01). Conclusions Ocular morbidities are common in children in Kavhrepalanchowk District with lid abnormalities being the most common issue, probably due to a lack of hygienic practice. Ethnic variation of ocular morbidities is an important observation mostly for refractive error and strabismus. http://dx.doi.org/10.3126/kumj.v8i4.6231 Kathmandu Univ Med J 2010;8(4):362-6